A conceptual model of information system usage for better improvement in organisations. (2016) - Magboul, Ibrahim Hussien Musa; Chew, Kok-Wai; Raman, Murali
This paper describes a conceptual model of information system (IS) usage for better improvement in organisations. First, the model considers IS usage as an intervening variable that plays a dual role, both as an antecedent and a consequence. Second, the model is constructed in context that reflects the essential factors influencing IS usage in organisations, namely, top management support, availability of training, business-IT alignment, information service support and IS investment. Third, the model integrates IS usage with selected strategic variables from the literature, namely, product differentiation, product innovation, process innovation, organisational performance, competitive advantage and strategy formulation in attempt to improve the performance of organisations. A number of propositions will be suggested based on the model as the basis for a future survey work to thoroughly examine, validate and refine the various aspects of IS usage.